Unified Fast-Dynamic Direct-Current Control Scheme for Intermediary Inductive AC-Link Isolated DC-DC Converters - Nie Hou; Yuzhou Li; Zhongyi Quan; Yun Wei Li; Andrew Zhou (IEEE Open Journal of Power Electronics, 2021)
The isolated dc-dc converters with middle inductive AC links dc-dc converter have been extensively studied in modern energy conversion applications for safety and reliability, especially those featuring intermediary inductive ac-link (I2ACL) configurations such as full-bridge dc-dc converter and dual-active-bridge (DAB). However, up to now, the dynamic equivalence in these I2ACL type converters has not been systematically revealed. To fill such a gap, in this paper, the existing I2ACL isolated dc-dc converters are reviewed thoroughly, including unidirectional type and bidirectional type. Then, the general current transferred features of these two groups are analyzed, respectively, and the transferred current during the transient process is just influenced by the middle inductance little. So, the I2ACL isolated dc-dc converter can be regarded as the first-order converter. Based on the discovered general characteristic, a unified fast-dynamic direct-current (FDDC) control scheme is proposed for improving the dynamic performance of these I2ACL isolated dc-dc converters. Such a scheme can also facilitate the uniform control design for existing or emerging new topologies with the same electrical equivalence. Moreover, the specialized design principles of the PI parameters in the unified FDDC control method are also presented. Finally, to verify the universality and feasibility of the proposed general FDDC control strategy, both simulation and experiment results are presented with demonstration examples, e.g., full-bridge type, DAB-type, and the three-phase DAB type dc-dc converters.